Morphological Analysis of The Derivational Suffix Found in Harry Potter and The Sorcerer's Stone by J. K. Rowling - Satria Pugar Alam (UPT Publikasi dan Penerbitan Universitas San Pedro, 2023)
This research aims to identify derivational suffix found in J.K. Rowling's novel entitled, Harry Potter and The Sorcerer's Stone. This research used descriptive qualitative method. This research research applied library research technique to collect the data. Furthermore, content analysis technique was applied to analyze the data. The result showed that there are 47 derivational suffixes which consist of 25 nominal suffixes (-age -ance, -ant, -ation, -dom, -ee, -ence, -er, -ful, -hood, -ian, -ing, -ion, -ist, -ity, -ment, -ness, -or, -ry, -ship, -sion, -ster, -ty, -ure, -y), 2 verbal suffixes (-en, -ize), 18 adjectival suffixes (-able, -al, -an, -ant, -ary, -ed, -en, -ful, -ian, -ible, -ic, -ing, -ish, -ive, -less, -ly, -ous, -y), and 2 adverbial suffixes (-ly, -ward). Those derivational suffixes can maintain, change, or even both.